Annual Plan 1966-67 Madras - Planning Commission (Planning Commission, 1973)
The Government of Madras have proposed an outlay of Rs. 260.50 lakhs for 1966-67 under the head ’Large and Medium Industries' . Out of the total of Rs. 260.50 a sum of Rs. 12.00 lakhs has been proposed for 'expansion of Geological Department' and hence does not come under the head of 'Large and Medium Industries'. Similarly a sum of Rs. 5.00 lakhs has been proposed for 'Investigation and Mining of Lead & Zinc ores', under new schemes. This again is to be considered under 'Mineral Development' . Besides, Rs. 92.50 lakhs has been proposed for Industrial financing out of .which Rs. 35.00 lakhs is for loans under State aid to Industries Act. This pertains to small scale sector and will be dealt with by the Working Group an small Scale Industries. Thus the provision left for large and medium industries is Rs. ’208.50, lakhs. The statement annexed indicates the provision made for 'large and medium industries' in the Third Plan, anticipated outlay during the Third Plan and the scheme wise outlay proposed for 1966-67 along with the foreign exchange requirements.
Programme Administration Division
Planning Commission
Keywords: Agricultural Programme; Minor Irrigation; Rural Electrification for increasing; Points for consideration; Modernising of Vagai Canal; Irrigation benefits; Power Projects; Physical Targets; Large & Medium Industries; Continuing Schemes; New Schemes